(untitled) (Applied Biological Research, 2023)
Hydroponics system is a potential and cost-effective technique for waste water treatment. Aquatic macrophytes are more efficacious material for phytoremediation due to their physiological and morphological properties. We designeset of three hydroponics (PVC pipes) interconnected in series o as the inlet of first hydroponic was connected from tank containing arsenic (As) contaminated wastewater and its outlet with the second as its inlet and outlet of second with the third one. In each hydroponic, 6 pots (filled with soil and compost and referred as semi-hydroponics systems viz., SHS-1, SHS-2 and SHS-3) with pre-established single individual of Phragmites australis, Colocasia esculenta and Canna indica were placed in SHS-1, SHS-2 and SHS-3, respectively. Wastewater was retained in each SHS for 10 days (hydraulic retention time); and passed from 1st to 2nd and then to 3rd one in series at every 10 days intervals. The growth performances of selected macrophytes were compared with and control plants maintained in freshwater hydroponics. Wastewater significantly enhanced shoot length, proline content, chlorophyll content and sugar content of leaf tissue of all the studied macrophytes. The plants and soil sediments absorbed As from the waste water efficiently and retained amount of As in phytoremediated spent wastewater from third semi-hydroponic system (SHS-3) was below limit of quantification of ICP-MS. The semi-hydroponic system in this experiment was found to be an efficient, cost-effective, easy to be installed and globally applicable phytoremediating technique.